2012
DOI: 10.1029/2012jd017638
|View full text |Cite
|
Sign up to set email alerts
|

Bright polar mesospheric clouds formed by main engine exhaust from the space shuttle's final launch

Abstract: [1] The space shuttle launched for the last time on 8 July 2011. As with most shuttle launches, the three main engines injected about 350 t of water vapor between 100 and 115 km off the east coast of the United States during its ascent to orbit. We follow the motion of this exhaust with a variety of satellite and ground-based data sets and find that (1) the shuttle water vapor plume spread out horizontally in all directions over a distance of 3000 to 4000 km in 18 h, (2) a portion of the plume reached northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…The table shows that space traffic released more H 2 O in 2011 than in any year since the beginning of the AIM mission. The effects of STS 135, launched on 8 July 2011 at 11:40 EDT, have already been documented, and it was shown that some of the brightest PMCs ever observed by CIPS and from the ground were formed from the main engine exhaust of this shuttle [ Stevens et al ., ]. This is consistent with not only the July 2011 enhancement we see here but also the occurrence of very high IWC in the 2011 SOFIE data (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The table shows that space traffic released more H 2 O in 2011 than in any year since the beginning of the AIM mission. The effects of STS 135, launched on 8 July 2011 at 11:40 EDT, have already been documented, and it was shown that some of the brightest PMCs ever observed by CIPS and from the ground were formed from the main engine exhaust of this shuttle [ Stevens et al ., ]. This is consistent with not only the July 2011 enhancement we see here but also the occurrence of very high IWC in the 2011 SOFIE data (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Our suggestion that the explanation lies in an H 2 O source from space traffic steps beyond previous discussions of this effect in three ways. First, previous reports have concentrated on relatively isolated events of PMC production by shuttle exhaust [e.g., Stevens et al ., , ]. Here we are suggesting that average PMC mass density and frequency, and its year‐to‐year variability from 2007 to 2012, are modulated by space traffic.…”
Section: Discussionmentioning
confidence: 99%
“…A water vapor plume leading to the formation of an exceptionally bright PMC has been observed in a variety of satellite and ground based data sets as result of emissions from the main engines from the space shuttle£s ¦nal launch in July 2011 [15]. Rocket emissions might explain the brightest fraction of the PMC population and interestingly larger ice particles were found above the smaller ones within the PMC.…”
Section: Polar Mesospheric Cloud Formation After Rocket Launchesmentioning
confidence: 97%
“…Stevens et al () looked at a subsequent Shuttle launch during the NH PMC season and identified a distinct postlaunch enhancement in PMC occurrence frequency and calculated IWC, using National Oceanic and Atmospheric Administration (NOAA)‐14 SBUV/2 PMC data. Shuttle‐related signals in PMC data have since been reported for five additional launches during the period 1999–2011 (Collins et al, ; Kelley et al, , ; Stevens et al, ; Stevens et al, ; Stevens et al, ). Table briefly summarizes these published results.…”
Section: Introductionmentioning
confidence: 98%